Kebijakan Pendidikan: Kebijakan Pendidikan: Kurikulum Pendidikan Nasional Era Soekarno sebagai Pembangunan Karakter Bangsa Indonesia 1945–1966 - Della Winka Septia; Siti Fatimah (Jurnal Kronologi, 2026)
This research focuses on the curriculum as a tool for national character building. This research explores educational policies during the Sukarno administration in 1945–1966. This aims to trace the development of the policy curriculum during that period, understand the ideological foundations that underlie it, and analyze the role of the curriculum in shaping the character and identity of the Indonesian nation after independence. This research uses a historical approach with a qualitative approach through the stages of heuristics, source criticism, interpretation, and historiography. The results show that during the Sukarno administration, the educational curriculum was aimed at developing a sense of nationalism, patriotism, and national personality in line with the state ideology. Education was not merely conveying knowledge, but also functioned as a political and ideological tool to shape Indonesians into nationalist, revolutionary, and character-based individuals. At that time, the policy curriculum was influenced by anti-imperialism, Indonesian socialism, and ideas about the state and character of development that became the basis for national development. The government aimed to create a generation with national awareness and loyalty to the state through subjects, educational activities, and the formation of national values. During this period, the educational curriculum underwent changes in accordance with the government's political direction, but its primary goal remained the same: helping shape the nation's character and national identity.